Phytoseiid mites of Japan (Acari: Mesostigmata) - Negm, Mohamed W.; Toyoshima, Shingo; Kishimoto, Hidenari; Amano, Hiroshi (Zootaxa, 2026)
A species list of phytoseiid mites (Acari: Mesostigmata: Phytoseiidae) in Japan is presented. The list was compiled from a survey of published literature, re-examination of accessible permanent slides, and from records obtained during field trips. A total of 97 taxa of phytoseiid mites, known to the species level, are so far reported as native to Japan. In addition, eight species are regarded as exotic, having been introduced into Japan. These phytoseiid mites are represented by the three subfamilies and 22 genera. The subfamily with the most known species is the Amblyseiinae Muma, with 64 species, among which 17 are in the genus Amblyseius Berlese, 15 in Neoseiulus Hughes, seven in Typhlodromips De Leon, four in Scapulaseius Karg & Oomen-Kalsbeek, three in each of Euseius Wainstein, Paraphytoseius Swirski & Schechter, and Proprioseiopsis Muma, two in each of Amblyseiulella Muma, Gynaeseius Wainstein, Okiseius Ehara, and Transeius Chant & McMurtry, and one in each of the genera, Amblydromalus (Garman & McGregor), Iphiseius Berlese, Phytoscutus Muma and Phytoseiulus Athias-Henriot. In the subfamily Phytoseiinae Berlese, there are 13 species of Phytoseius Ribaga, while the subfamily Typhlodrominae Wainstein, is represented by 28 species, of these, 23 in Typhlodromus and one species in each of the genera, Chanteius Wainstein, Galendromus Muma, Kuzinellus Wainstein, Paraseiulus Muma and Typhlodromina Muma. Identification keys to subfamilies, tribes, genera and species of the Phytoseiidae in Japan are presented.